2016
DOI: 10.13075/ijomeh.1896.00725
|View full text |Cite
|
Sign up to set email alerts
|

Lost-time illness, injury and disability and its relationship with obesity in the workplace: A comprehensive literature review

Abstract: The objective of this study was to conduct a literature review examining predictors of lost-time injury, illness and disability (IID) in the workplace, with a focus on obesity as a predictor, and to evaluate the relationship between obesity and losttime IID. The study objective was also to analyze workplace disability prevention and interventions aimed at encouraging a healthy lifestyle among employees and reducing obesity and IID, as well as to identify research gaps. The search was conducted in several major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Perioperative workers also should strive to maintain a healthy weight. A synthesis of the international research literature concluded that workers with a body mass index greater than 30 had higher rates of workplace injury and slower recovery times compared to workers with healthy weights 41 . Finally, we believe that perioperative staff members—like all health care workers—need to get proper sleep and exercise and effectively manage stress.…”
Section: Implications For Perioperative Nursesmentioning
confidence: 89%
“…Perioperative workers also should strive to maintain a healthy weight. A synthesis of the international research literature concluded that workers with a body mass index greater than 30 had higher rates of workplace injury and slower recovery times compared to workers with healthy weights 41 . Finally, we believe that perioperative staff members—like all health care workers—need to get proper sleep and exercise and effectively manage stress.…”
Section: Implications For Perioperative Nursesmentioning
confidence: 89%
“…For instance, studies have found obesity negatively impacting on perceived job suitability [ 9 ]. In contrast, some adverse impacts are thought to arise specifically as a consequence of poor health, with obesity linked to greater sickness absence due to illness, injury and disability [ 10 ].…”
Section: Introductionmentioning
confidence: 99%